Triggered massive star formation associated with the bubble HII region Sh2-39 (N5) - Duronea, Nicolás Urbano (2017)
Aims. We perform a multiwavelength analysis of the bubble Hii region Sh2-39 (N5) and its environs with the aim of studying the physical properties of Galactic IR bubbles and exploring their impact in triggering massive star formation. Methods. To analyze the molecular gas, we used CO(3-2) and HCO+(4-3) line data obtained with the on-the-fly technique from the ASTE telescope. To study the distribution and physical characteristics of the dust, we made use of archival data from ATLASGAL, Herschel, and MSX, while the ionized gas was studied making use of an NVSS image. We used public WISE, Spitzer, and MSX point source catalogs to search for infrared candidate young stellar objects (YSOs) in the region. To investigate the stellar cluster [BDS2003]6 we used IR spectroscopic data obtained with the ARCoIRIS spectrograph, mounted on Blanco 4 m Telescope at CTIO, and new available IR Ks band observations from the VVVeXtended ESO Public Survey (VVVX). Results. The new ASTE observations allowed the molecular gas component in the velocity range from 30 km s-1 to 46 km s-1, associated with Sh2-39, to be studied in detail. The morphology of the molecular gas suggests that the ionized gas is expanding against its parental cloud. We identified four molecular clumps, which were likely formed by the expansion of the ionization front, and determined some of their physical and dynamical properties. Clumps with HCO+ and 870 μm counterparts show evidence of gravitational collapse. We identified several candidate YSOs across the molecular component. Their spatial distribution and the fragmentation time derived for the collected layers of the molecular gas suggest that massive star formation might have been triggered by the expansion of the nebula via the collect and collapse mechanism. The spectroscopical distance obtained for the stellar cluster [BDS2003]6, placed over one of the collapsing clumps in the border of the Hii region, reveals that this cluster is physically associated with the nebula and gives more support to the triggered massive star formation scenario. A radio continuum data analysis indicates that the nebula is older and expands at lower velocity than typical IR Galactic bubbles.